Investigating the Connections Between Food Choices and Climate Change Mitigation in Fijian Households - Kaminski, Alexandra; Hughes, Peter; Sevakarua, Waisiki; Dukuno, Osea; Kamanalagi, Joana; Glover, Mia; Drew, Joshua (Ethnobiology Letters, 2025)
Climate change negatively impacts Indigenous people’s food sovereignty. The choices communities make to manifest that sovereignty fluctuate in response to environmental conditions and access to resources. To investigate how communities in coastal Indigenous Fijian (iTaukei) villages balance risks related to food production and food access we conducted 71 interviews in three coastal communities across Fiji. We asked which foods were purchased from nearby towns, which foods were grown or harvested locally, and how different spatial locations and climatic factors affected food choices. Geography, weather patterns, and extreme events influence food production, while village remoteness influences food access. These factors also affect risk exposure mitigation in iTaukei communities. Our cluster analysis comparing food items in town and village groups showed there was little overlap between community-grown and purchased foods for each village. However, there was a higher degree of variation within the community-grown foods. Purchased food and frequency of travel were consistent among all locations regardless of distance or cost of travel, suggesting that items from towns were relatively inelastic to travel costs. We find that coastal iTaukei communities are splitting risks by maintaining two complementary food systems, providing the ability to alternate between purchased and community-grown foods to adjust for varying risk levels. While grounded in Fiji, this work speaks to broader conversations about barriers to Indigenous food sovereignty.